Consumers’ awareness and practices towards ‘exclusion clause’ and its position under Islamic law - Abu Bakar, Elistina; Amin, Naemah (2015)
The aim of this paper is to explore the consumers’ awareness and practices towards ‘exclusion clause. The underlying philosophy is that consumers are free to enter into contracts and therefore must take care of their own interests. The results of this study show that only 41.8% from 400 respondents in Klang Valley aware of the existence of such clauses in their dealing with the suppliers and 50.8 % of the respondents responded that they did not understand the implication of such clause. In total, 54.3% of them stated that they would still sign the document even though they were already aware of the exclusion clauses or any other unfair contractual terms. The Islamic law of mu‘āmalāt has also been referred to look at the extent to which Islamic law has provided protection to consumers in relation to exclusion clauses. Malaysia should adopt these principles into consumer policy and legislation so as to strengthen the consumer protection in the country.